2011
DOI: 10.1007/s11270-011-0836-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seven Fungicides on Non-Target Aquatic Fungi

Abstract: Aquatic risk assessments for fungicides are carried out without information on their toxicity to non-target aquatic fungi. This might cause an underestimation of the toxic effects to the aquatic fungal community. This study focuses on the question whether recently derived concentrations limits for fungicides considered to protect populations of primary producers and (in)vertebrates also do protect the aquatic fungi. A panel of fungal species and Oomycetes was isolated and identified from unpolluted surface wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 10 publications
(20 reference statements)
4
56
0
1
Order By: Relevance
“…The imidazole fungicide, imazalil, reduced the sporulation of Heliscella stellata, Lunalospora curvula , and other sigmoid type-2 aquatic fungi at concentrations ranging between 0.1–100 µg L −1 (Flores et al, 2014). Imazalil also had a EC 100 on aquatic fungi at concentrations ranging from 10 000 to 210 000 µg L −1 (Dijksterhuis et al, 2011). The fungicide chlorothalonil (at 0.0176–1.76 and 32–176 µg L −1 ) reduced the growth of Batrachochytrium dendrobatidis in culture and on infected tadpoles (McMahon, Romansic, and Rohr, 2013).…”
Section: Specific Effects Of Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The imidazole fungicide, imazalil, reduced the sporulation of Heliscella stellata, Lunalospora curvula , and other sigmoid type-2 aquatic fungi at concentrations ranging between 0.1–100 µg L −1 (Flores et al, 2014). Imazalil also had a EC 100 on aquatic fungi at concentrations ranging from 10 000 to 210 000 µg L −1 (Dijksterhuis et al, 2011). The fungicide chlorothalonil (at 0.0176–1.76 and 32–176 µg L −1 ) reduced the growth of Batrachochytrium dendrobatidis in culture and on infected tadpoles (McMahon, Romansic, and Rohr, 2013).…”
Section: Specific Effects Of Pesticidesmentioning
confidence: 99%
“…The fungicide chlorothalonil (at 0.0176–1.76 and 32–176 µg L −1 ) reduced the growth of Batrachochytrium dendrobatidis in culture and on infected tadpoles (McMahon, Romansic, and Rohr, 2013). Chlorothalonil was also toxic to aquatic fungi with an EC 100 at concentrations exceeding 260 µg L −1 (Dijksterhuis et al, 2011). Also, although exceeding environmentally relevant concentrations, the phosphanoglycine fungicide, thiophanate methyl, significantly decreased the zoosporangia number of Batrachochytrium dendrobatidis at 1500 µg L −1 (Hanlon and Parris, 2012).…”
Section: Specific Effects Of Pesticidesmentioning
confidence: 99%
“…Although these stressors were not measured, previous studies in streams of our sampling region reported fungicide concentrations (e.g. Bereswill et al, 2012;Fernández et al, 2014) that can affect microorganisms (Dijksterhuis et al, 2011). To sum up, a multiple stressor complex including pH, nutrients, sedimentation and toxic agrochemicals may have influenced the response of OMB micro (Bärlocher, 1992).…”
Section: Organic Matter Breakdown and Land Usementioning
confidence: 82%
“…Besides, as azoles can affect the ergosterol biosynthesis, may be studied its effects for non target organisms present in the application area (Dijksterhuis et al, 2011). As one of them, Tebuconazole is a systemic triazole classified by USEPA as carcinogenic for human beings (Konwick et al, 2006;Hu et al, 2007) and toxic for aquatic organisms (Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%